2018
DOI: 10.2147/ppa.s149081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anterior crowding or spacing on oral health-related quality of life: a cross-sectional study

Abstract: IntroductionOral health-related quality of life (OHRQoL) involves many aspects such as chewing ability, sleeping, social interactions, self-esteem, and satisfaction with life and oral health. The increasing research interest in OHRQoL began only after the shortcomings of previous approaches of treating symptoms only and neglecting the patient’s self-perception were revealed.Patients and methodsThe current study design is a cross-sectional study of patients who attended King Abdulaziz University Dental Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
(29 reference statements)
2
8
0
Order By: Relevance
“…Children from lower-income families were more likely to report a negative impact on functional limitations, emotional well-being, and social well-being. The results corroborated previous studies 24,27 and showed that underprivileged children had less access to dental treatment, which had a negative influence on OHRQoL. Also, malocclusion and its impact on OHRQoL might be influenced by the local health care system, 13 which adds to the explanation of the differences in the association of malocclusion with OHRQoL among various populations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Children from lower-income families were more likely to report a negative impact on functional limitations, emotional well-being, and social well-being. The results corroborated previous studies 24,27 and showed that underprivileged children had less access to dental treatment, which had a negative influence on OHRQoL. Also, malocclusion and its impact on OHRQoL might be influenced by the local health care system, 13 which adds to the explanation of the differences in the association of malocclusion with OHRQoL among various populations.…”
Section: Discussionsupporting
confidence: 89%
“…The findings rejected the study hypothesis because, even when the quality of life was evaluated based on the item levels, the anterior occlusal characteristics in the mixed dentition had no impact on the OHRQoL. Previous studies 3,4,7,8,[20][21][22][23][24][25][26][27][28][29] showed that an increased overjet and increased spacing, especially a midline diastema, were the conditions that most affected the individual, regardless of age. Still, the older children become, the more their malocclusion affects their a Values are given as n (%).…”
Section: Discussionmentioning
confidence: 87%
“…The Arabic OHIP-14 has been used in previous studies to assess the quality of life with different malocclusions. 17,24,26 In our study we found a statistically significant association between anterior vertical discrepancy in occlusion and embarrassment (p = 0.001), followed by being selfconscious about their appearance, discomfort while eating (p = 0.009), generalized mouth aching (p = 0.012), and speech problems (p = 0.049). These findings are in line with those of previous studies that evaluated OHRQoL in different malocclusions.…”
Section: Discussionsupporting
confidence: 49%
“…Spacing and smaller teeth could also be aesthetically problematic. Especially anterior spacing might impact Oral Health Related Quality of Life negatively and increase self-consciousness about one's appearance [52][53][54]. Moreover, when permanent teeth are not matched for size, normal occlusion might be difficult to achieve [10].…”
Section: Plos Onementioning
confidence: 99%